PENGENALAN DIGITAL MARKETING DALAM UPAYA OPTIMALISASI PEMASARAN PADA UMKM DI DUSUN GIRIMULYO - A’yun, Efrida Qurotul; Piero, Alessandro Adrian; Nisa, Ayu Sofi Khairul; Nazhifah, Dafina; Orvala, Edelweis Zita; Erowati, Endang; Kinanthi, Gendis Surya; Ma’ruf, Muhammad Nur Fatah; Sidiq, Muhammad Rais; Billa, Shaqhirra Diva Salsa; Latifah, Emmy (Lembaga Penelitian, Publikasi Ilmiah dan Pengabdian kepada Masyarakat (LP3M), 2024)
With the rapid development of technology and the internet, the marketing world is experiencing a significant transformation. Optimizing and utilizing digital marketing helps in the product marketing activities of a business and the activities of tiny and medium enterprises. Realizing this potential, the UNS 336 KKN Team aims to help market UMKM in Girimulyo Hamlet, Trengguli Village, Jenawi District, Karanganyar, by adopting and optimizing digital marketing techniques to increase the visibility and sales of their products. The activities include socialization and training on marketing digitalization through various platforms such as e-commerce, Google Maps, e-wallet, and social media. The results of this program show a significant increase in the understanding and ability of UMKM players to utilize digital marketing tools. Several UMKM have succeeded in creating online business accounts, increasing visibility on Google Maps, and starting to use social media to promote their products. In conclusion, this marketing digitalization program has the potential to be an essential catalyst in local economic development in Girimulyo Hamlet, with recommendations for continued assistance and further training to ensure the continued adoption of digital technology by local UMKM.